EFFECT OF AFLATOXINS ON GOATS MILK PRODUCTION AND ITS CHEMICAL AND PHYSICAL COMPOSITION (Mesopotamia Journal of Agriculture)
This study was conducted to show the effects of each aflatoxins (AF) or activated sodum bentonite(AB) .Singly or combination in the following groups:1- animals fed Diet (AF) alone at 2.5mg/kg.2-animal fed died (AF)at 2.5mg/kgwith AB(5g/kg). 3-animals fed diet AB alone (5g/kg).The result show that the effect of AFB1 on physical characteristics were investigated. The toxin caused changes in the physical characteristics of milk. Viscosity, density, curd tension and acidity of the produced milk were significantly (p<0.05) decreased while the pH and coagulation time were significantly increased. Addition of ASB proved to have a positive effect on the AFB1-treated animals. physical characteristics became closer to the normal milk. Ceasing AFB1- contaminated feed consumption by the animals also resulted in physical characteristics of the produced milk to normal.